Clinical and Molecular Investigation of Familial Multiple Lipomatosis: Variants in the HMGA2 Gene - Mejía Granados DM; de Baptista MB; Bonadia LC; Bertuzzo CS; Steiner CE (Dove Medical Press, 2020)
Diana Marcela Mejía Granados, Marcella Bergamini de Baptista, Luciana Cardoso Bonadia, Carmen Silvia Bertuzzo, Carlos Eduardo Steiner Department of Medical Genetics and Genomic Medicine, School of Medical Sciences, University of Campinas, Campinas, São Paulo, BrazilCorrespondence: Diana Marcela Mejía GranadosDepartment of Medical Genetics and Genomic Medicine, School of Medical Sciences, University of Campinas, Rua Tessália Vieira De Camargo 126, Cidade Universitária, Campinas, São Paulo 13083-887, BrazilTel +55 19 9 7151-1695Email d164712@dac.unicamp.brBackground: Familial multiple lipomatosis (FML) is an autosomal dominant disorder characterized by the slow growth of encapsulated nodules spread across the trunk and limbs. Currently, there is no specific etiology; therefore, its molecular and biological bases need to be better understood. High-throughput sequencing technologies appear to be a cost-effective tool and have a pivotal role in elucidating different genodermatoses.Objective: This study aimed to perform a clinical and molecular characterization of constitutional DNA of seven individuals belonging to five unrelated families diagnosed with FML.Patients and methods: Clinical aspects were obtained from medical records and physical examination. HMGA2 gene was investigated using Sanger sequencing method. Mutational analysis of other genes associated with syndromic lipomatosis AKT1, APC, PIK3CA, MEN-1, and PTEN was performed through next-generation sequencing.Results: In this series, FML was predominant among women who were overweight and reaching the age of thirty and was associated with gastrointestinal comorbidity. Histopathological diagnosis of biopsies revealed typical features of both lipoma and angiolipoma. We identified two identical novel variants with unknown significance in exon 5 of the HMGA2 gene in two participants of different families. There were no additional changes in exons 1 to 4 of the HMGA2 gene. Multi-gene panel was normal in all cases.Conclusion: Variants found in exon 5 of the HMGA2 gene have not been described and have an uncertain significance in the genesis of FML. Further studies, including a more significant number of affected individuals and functional analysis of the novel variants of HGMA2 gene, should be undertaken to better understand its biological role in FML.Keywords: HMGA2 gene, next-generation sequencing, familial lipomatosis